Implementación de una estrategia de Customer Relationship Management para la gasolinera Petroecuador “Merceditas”, del cantón Mera, provincia de Pastaza, año 2022 - Alarcón Gavilanes, María Gabriela (2023)
This research work develops the Implementation of a Customer Relationship Management Strategy for the PetroEcuador Gas Station "Merceditas", in the Mera Canton, Pastaza Province, Year 2022. In this company there is no Customer Relationship Management (CRM) strategy to automate processes, build customer loyalty and reach consumers directly. Likewise, it did not have preventive and corrective maintenance of its dispensers. In this aspect, the general objective of the research is to implement a Customer Relationship Management strategy to ensure an intimate relationship with customers and meet their needs, using a technological system and digital platforms. For its execution the type of exploratory, descriptive and field research was used, the approach was quantitative and qualitative with a deductive method; the population taken for this study is made up of monthly customers who come to the gas station to which the survey was applied, an interview was conducted with the owner and, finally, to know their current situation an internal and external analysis was developed. The project is feasible because by automating the processes it was possible to acquire a database of customers, which made it possible to identify their needs and make the decision to satisfy them.